Selected properties of core-buildup materials for prosthetic restorations - Badawy, Rania; Justus Liebig University Giessen (My University, 2011)
The aim of this study was to test four hypotheses, divided into two parts:In the 1st Part of the study, the flexural properties (flexure- strength (FS) and flexuralmodulus(FM)) of 4 different groups of tooth-colored core-buildup materials (glassionomers:conventional-and metal-modified, resin-modified glass-ionomers, polyacidmodifiedcomposite resins (compomers) and composite resins: self-, light- and dualcured,were investigated, testing the effect of different variables (material type, storagetime and condition, and the curing mode) on flexural properties. Moreover, the effect ofthe light-curing step on 3 dual-cured materials (a resin-modified glass-ionomer and 2composite resins) was investigated, comparing their flexural properties with and withoutlight-curing.A total of 850 bar-shaped specimens (25 mm x 2mm x 2mm) were tested in a 3-pointbendingtest device, after storage under 5 different conditions (10 min dry in an incubator(baseline) to be additionally stored for either 2h,24h and 7d in deionized water (37°C/7dthermocycling with 5000 cycles at 5-55°C).From the results it can be concluded that several variables influence the flexuralproperties of the 4 groups of tooth-colored core-buildup materials. The type of material(glass-ionomer or resin-based), storage condition, as well as light-curing, significantlyinfluences flexural properties of the 4 groups of tooth-colored restorative materials,showing higher flexural properties (FS and FM) for resin-based materials and lightcured-types compared to chemically-cured types.In the 2nd Part of the study the relationship between the flexural properties (FS and FM)and the degree of conversion as well as the influence of storage condition on the degreeof conversion of 7 different composite resin materials were assessed.A total of 280 bar-shaped specimens were tested. The degree of conversion wasdetermined by calculating the percentage of reacted C=C bonds using an FTIR analysis(baseline method) on the fractured bar-shaped specimens immediately after recording theflexural properties. Prior to testing, the specimens were subjected to 8 different storageconditions (5 min and 10 min dry storage in an incubator at 37°C, in distilled water at37°C for 1h, 4h, 24h, 2d, 7d and 7d thermocycling after being stored for 10 min asbaseline in an incubator at 37°C).The bivariate correlation analysis revealed a significant relationship (p<0.05) between% DC and flexural properties (FS and FM) for 3 materials: 2 self-cured compositeresins (Luxa Core Automix and Clearfil Core New Bond) as well as Rebilda DC, thedual-cured composite resin, while the rest of composite resins revealed no correlationbetween both parameters.For the influence of storage condition on the degree of conversion, a significant (p <0.05) yet weak (r2 < 0.25) correlation between both parameters was recorded for allcomposite resins, except for Luxa Core Automix Dual, the dual-cured composite resin,which revealed no correlation between both parameters (p > 0.05).From the results it can be concluded that degree of conversion does not reflect themechanical properties for all composite resins equally, and that in contrast to the 7 daystorage period in distilled water, which obviously influenced both flexural properties,the thermocycling period revealed no influence on the DC values for all compositeresins tested.

Das Ziel dieser Studie war es, vier Hypothesen, unterteilt in zwei Teile, zu untersuchen:Im 1.Teil der Studie, wurden die Biegeeigenschaften (Biegefestigkeit (FS) undBiegemodul (FM) von 4 verschiedener Gruppen zahnfarbener Kernaufbau-Materialien(Glas-Ionomere: konventionell-und Metall-modifiziert, Harz-Glas-Ionomere, PolysäuremodifizierteKomposite (Kompomere) und Komposit-Harze: selbst-, Licht- unddualhärtend) untersucht. Der Effekt verschiedener Variablen (Materialart, Lagerzeit undZustand, und das Härtungsverfahren) auf die Biegeigenschaften wurde getestet. Darüberhinaus, wurde die Wirkung des Lichthärtungsverfahrens auf 3 dual-gehärtete Materialienuntersucht (ein hazmodifiziertes Glasionomerzement und 2 Komposit-Harze), wobeideren Biegeeigenschaften (FS und FM) mit- und ohne Lichthärtung verglichen wurden.Insgesamt wurden 850 stabförmige Proben (25 mm x 2mm x 2mm) in einem 3-Punkt-Biegeversuch getestet, nachdem diese einer Lagerung unter 5 verschiedenenBedingungen (10 min trocken in einem Brutschrank (Basislinie), und dann einezusätzliche Lagerung entweder für 2h, 24h und 7d in deionisiertem Wasser (37 ° C/7dThermocycling mit 5000 Zyklen bei 5-55 ° C) ausgesetzt waren.Aus den Ergebnissen lässt sich schließen, dass mehrere Variablen die Biegeeigenschaftender 4 Gruppen von zahnfarbenen Kern-Aufbau Materialien beeinflussen. Die Art desMaterials (Glasionomer oder Harz-basiert), Lagerungsbedingungen sowie dasHärtungsverfahren, beeinflusst die Biegeeigenschaften der 4 Gruppen maßgeblich, wobeiHarz-basierte Werkstoffe sowie Lichthärtende - Materialien höhere Biegeeigenschaften(FS und FM) im Vergleich zu den chemischhärtenden Materialien zeigten.Im 2. Teil der Studie wurden die Beziehung zwischen der Biegeeigenschaften (FS undFM) und dem Umsetzungsgrad (%DC), sowie der Einfluss der Lagerungsbedingungenauf den Umsatzungsgrad (%DC) 7 verschiedener Komposit Materialien bewertet.Insgesamt wurden 280 stabförmige Proben getestet. Der Grad der Umsetzung wurde alsAnteil (Prozent) der umgesetzten C=C- Bindungen mit Hilfe einer FTIR - Analyse(Baseline-Methode) der gebrochenen stabförmigen Proben sofort nach der Aufnahme derBiegeeigenschaften bestimmt. Vor der Prüfung wurden die Proben 8 verschiedenenLagerbedingungen (5 min und 10 min trockene Lagerung in einem Brutschrank bei 37 °C, in destilliertem Wasser bei 37 ° C für 1h, 4h, 24h, 2d, 7d und 7d Thermocyclingnach einer Lagerung in einem Brutschrank bei 37 ° C als Basislinie) ausgesetzt.Die bivariate Korrelationsanalyse ergab eine signifikante Beziehung (p<0,05) zwischen% DC und Biegeeigenschaften (FS und FM) für 3 Materialien: 2 selbsthärtendeKomposit-Harzen (Luxa Core Automix und Clearfil Core New Bond) sowie dasdualhärtende Rebilda DC, während die anderen Komposit Materialien keine Korrelationzwischen beiden Parametern zeigte.Bezüglich des Einflusses der Lagerungsbedingungen auf den Umsetzungsgrad, war einesignifikante (p < 0,05) doch schwache (r2 < 0,25) Korrelation zwischen beidenParametern für alle Komposit - Harze festzustellen. (Ausnahme: Luxa Core AutomixDual)Aus den Ergebnissen lässt sich schließen, dass der Umsetzungsgrad nicht diemechanischen Eigenschaften für alle Komposit Materialien gleichermaßen widerspiegelt,und dass im Gegensatz zu einer 7 Tagen Lagerungszeit in destilliertem Wasser, welchedie % DC-Werte aller untersuchten Komposit-Harzen beeinflusste, zeigte Thermocyclingkeinen Einfluss auf die % DC-Werte der Komposit Materialien.
Ausgewählte Eigenschaften von Aufbaumaterialien für prothetische Restaurationen
Keywords: core-buildups; tooth-colored; flexural properties; degree of conversion; thermocycling; ddc:610